THE INFLUENCE OF EMPLOYEE COMPETENCE, ORGANIZATIONAL COMMITMENT, PERSONAL COST AND LEGAL PROTECTION ON WHISTLEBLOWING FOR FRAUD PREVENTION - Manurung, Lucy; Kristanti, Putriana (LPPM STIE Muhammadiah Bandung, 2024)
This study aims to empirically examine the effect of employee competence (KP), organizational commitment (OCM), personal cost (PC), and legal protection (LP) on whistleblowing. Whistleblowing is a system that can be used to report fraud that occurs based on accurate facts and evidence. This study uses primary data in the form of questionnaires distributed online and directly. The samples of this study were principals, vice principals, teachers, and staff of public and private high schools in 5 sub-districts of Yogyakarta City, namely Gondokusuman, Umbulharjo, Gondomanan, Kotagede, and Tegalrejo sub-districts. The data analysis method used is Structural Equation Modeling (SEM). The results of this study obtained 263 respondents and showed that employee competence does not affect whistleblowing, while organizational commitment, personal cost, and legal protection affect whistleblowing. This means that high school employees in the Yogyakarta City neighborhood already have the intention of whistleblowing. It is recommended that officials can improve facilities for employees to carry out whistleblowing if needed by more easily reducing risk (personal cost).